The Iraqi-Syrian unity project in 1979 - Amayreh, Mohammed Salem; Al-Jabali, Khaled Hassan; Alshrieda, Khaled Suleiman Hamad (Journal of Ecohumanism, 2024)
This study focused on the Syrian-Iraqi unity project, which was launched by the governments of Iraq and Syria in 1978. Thus, the research explored the reasons that caused the desire for Iraqi and Syrian unity. The research also cleared the Zionist, international, and Arab positions on the Syrian-Iraqi project. Furthermore, the study pointed out the position of the Soviet Union in the project which was positive for it. On the other side, the United States of America and the Zionist entity made a concerted effort to undermine this project. The idea was unsuccessful and remained a dead letter as a consequence of American and Zionist opposition